Commitment to Criticism - Richard, Taylor (2013)
The nature of literary criticism and role of the critic is largely dependent on an acceptable definition of literature itself. One view which has been fairly widely held is that literature is the expression of intense and personal experience in a unique and original form which collectively reflects the values and aspirations of a given people in a particular time and place. An individual work externalizes and eternalizes the writer's perceptions of both the self and the world outside. The critic's role is to interpret works of literature to the public at large; not merely to describe or explain them, but rather to comment on and evaluate the quality of both the author's literary composition and his vision of, or insight into, human experience. In his or her quest for excellence and truth the critic should function as an educator, not as a popularizer or purveyor of culture. Serious criticism is evaluative, not descriptive, and the responsibility of the critic is to engage the artist in a public debate for the mutual benefit of all concerned. One of the more important arguments in this dialogue concerns the question of taste, the reader's apprehension and acceptance of style and structure as they change and evolve.